Meat Reduction Practices in the Context of a Social Media Grassroots Experiment Campaign - Pasi Pohjolainen; Pekka Jokinen (MDPI, 2025)
High meat consumption appears regularly in sustainability discourses but finding practical tools for reduction has proven to be challenging. The rise of social media has opened up new pathways to structure political spaces where grassroots initiatives for experiments can take place. Our paper examines how consumer-citizens started experimenting with vegetarian foods in the context of an innovative Finnish meat reduction social media campaign called Meatless October during its kick-off year in 2013. The focus is on participants' perceptions of the campaign and reflections of the experiment process. We analyzed participants' blog posts by using a qualitative content analysis. Our results show that the participants were often strongly motivated by the campaign's sustainability frame. They also saw the campaign both as a communal challenge and an opportunity for political action, sharing know-how and experiences with the other participants. In everyday life, participants' main focus and worry were in being able to prepare tasty and healthy vegetarian foods, and they were positively surprised by their ability to learn these skills. Participants typically attributed both success and failure in experimenting to their individual capabilities. Overall, our study suggests that the campaign's public context pushed private practices towards change by facilitating the experimenting process.